Building One-dimensional P-wave velocity model for the northern part of North West Region of Vietnam - Sơn, Lê Tử; Giang, Hà Thị; Văn, Đinh Quốc (Vietnam Journal of Earth Sciences, 2012)
The 1D P-wave velocity model and station corrections were computed by Simultaneous Inversion/Coupled Hypocenter-Velocity Model Algorithm (Kissling E. at all, 1994) and the data set of 135 local earthquakes (located with a minimum of 5 observations and an azimuthal gap ≤ 180°) for the northern part of North West Region of Vietnam. Based on available research, initial P- wave velocity model contained of 17 layers was built with P wave velocity by 5.0km/s for first layer and by 8.0km/s for Moho with 32km of depth. For shallow crustal levels, thickness of the first layers is taken from 1 to 2 km. The layer thickness is increased gradually with increasing depth to about 4 to 5km at Moho depth. The ratio Vp/Vs = 1.71 is determined by Wadati method using seismic data in the northern part of North West region of Vietnam. After many VELES runs, we get a simpler model that comprise of 8 layers by combining layers where velocities are very similar. Using this velocity model and the program HYPOCENTER 3.2 (Lienert, 1994), we relocated a set of 135 local events. The comparison between previous earthquake locations and new relocated shows a good improvement and the RMS of the location errors are reduced that indicates the stability of the new model.